Is Uro-oncological Surgery Safe During the COVID-19 Pandemic? Comparative Morbidity and Mortality in Patients Undergoing Surgery 2019-2020: Safety of uro oncological surgery during the pandemic - Bravo, Juan Cristóbal; Navarro, Renato; Rojas, P; Hinrichs, Laura; Schalper, Maximiliano; Zuñiga, Alvaro; San Francisco, Ignacio (Urology Journal, 2021)
Introduction: The SARS-CoV-2 infection has resulted in an unprecedented pandemic. Patients undergoing surgery are a group at risk of exposure. Also, patients with ongoing infection undergoing surgery may be more susceptible to developing complications. There is no significant data on surgical safety in the pandemic period. Material and Methods: Observational study based in a prospective database of urological oncological surgery. Data were obtained during the 2020 mandatory confinement period compared to the same period in 2019. The records were reviewed 45 days post-surgery. The objective was to compare surgical morbidity and mortality during the pandemic versus an average year in urological cancer surgery. Results: During confinement period (2020), 85 patients underwent uro-oncology surgery, while in 2019, during the same period, 165. The Clavien-Dindo morbidity ≥3 in 2020 was 2.3% (n=2), and in 2019, it reached 6% (n=10). In 2020, 9 patients were readmitted (10.5%). One patient (1.1%) was re-interfered, with a perioperative mortality of 1.1%. In 2019, 21 patients (12.7%) were readmitted. Seventeen patients (10.3%) were re-interfered, with a perioperative mortality of 1.8%. The median number of days hospitalized was 2 (IQR=2) in 2020 and 3 (IQR=3) in 2019. No significant differences were found in population or morbimortality, except for reoperation in a normal year. Conclusion: Postoperative morbidity and mortality reported are lower than those shown in the literature concerning COVID-19 and similar to that historically reported by our centers. This study suggests that it is safe to operate patients with urological cancer following the appropriate protocols during a pandemic.